Galectin-9 – ligand axis: an emerging therapeutic target for multiple myeloma - Shil, Rajib K.; Mohammed, Norhan B. B.; Dimitroff, Charles J. (Frontiers in Immunology, 2024)
Galectin-9 (Gal-9) is a tandem-repeat galectin with diverse roles in immune homeostasis, inflammation, malignancy, and autoimmune diseases. In cancer, Gal-9 displays variable expression patterns across different tumor types. Its interactions with multiple binding partners, both intracellularly and extracellularly, influence key cellular processes, including immune cell modulation and tumor microenvironment dynamics. Notably, Gal-9 binding to cell-specific glycoconjugate ligands has been implicated in both promoting and suppressing tumor progression. Here, we provide insights into Gal-9 and its involvement in immune homeostasis and cancer biology with an emphasis on multiple myeloma (MM) pathophysiology, highlighting its complex and context-dependent dual functions as a pro- and anti-tumorigenic molecule and its potential implications for therapy in MM patients.